Antecipation and the Time-Consistency of Fiscal Policy - Lang, Günther (2019)
This paper is concerned with the question of the existence of stationary Markov-perfect equilibrium in an overlapping generations growth model in the tradition of Diamond [19651, where in each period a government is in power, being interested in maximizing a social welfare function which consists of a weighted sum of utilities of those generations only who are alive in this period. This setting causes conflicts of interest between two succeeding governments and implies time-inconsistency of optimal plans made by myopic planners. If these planners are non-myopic, however, they will take into account the reaction of their successors. We will therefore ex-amine what game-theoretic concept can be applied, whether game equilibria exist. and what their properties are.